Understanding the Purchase Decisions Made by Generation Z on Shopee - Futri Safhira; Gustian Djuanda (Majapahit Journal of Islamic Finance and Management, 2026)
The rise of e-commerce has transformed Generation Z's (born 1997-2012) shopping patterns, with Shopee as Indonesia's leading platform due to free shipping and promotions. This study identifies purchase decision factors, UX/UI design, trust, promotions-discounts, social influence, and price-product variety using Analytic Hierarchy Process (AHP) as a novel alternative to prior regression or SEM. Survey data from 31 Gen Z Shopee users in Sukabumi (simple random sampling) were converted to Saaty scale, analyzed via pairwise matrices, eigenvalue, and Consistency Ratio (CR=0.0119). Findings: price and product variety dominate (weight 6.25), followed by social influence (5.19), UX/UI (4.89), trust (4.87), and promotions-discounts (4.06). E-commerce strategies should prioritize pricing, product diversity, and social trends for Gen Z.